2015
DOI: 10.1002/pmic.201400505
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in abundance of specific membrane proteins of Aggregatibacter actinomycetemcomitans is attributed to deletion of the inner membrane protein MorC

Abstract: Aggregatibacter actinomycetemcomitans is an important pathogen in the etiology of human periodontal and systemic diseases. Inactivation of the gene coding for the inner membrane protein, morphogenesis protein C (MorC), results is pleotropic effects pertaining to the membrane structure and function of this bacterium. The role of this protein in membrane biogenesis is unknown. To begin to understand the role of this conserved protein, stable isotope dimethyl labeling in conjunction with mass spectrometry was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 43 publications
0
28
2
Order By: Relevance
“…Disruption of this secretion system results in a reduction of the virulence potential of a number of bacteria including Klebsiella pneumoniae, Proteus mirabilis, Citrobacter rodentium and Salmonella enterica (Burall et al, 2004;Selkrig et al, 2012;Struve et al, 2003). The TamA/B complex is required for the efficient secretion of specific autotransporter proteins to the outer membrane in Enterobacteriaceae (Selkrig et al, 2012), in contrast to what is observed in morC mutants of A. actinomycetemcomitans, which express WT levels of known autotransporters (Smith et al, 2015a), which can easily be visualized by electron microscopy (Azari et al, 2013;Gallant et al, 2008).…”
Section: Introductionmentioning
confidence: 75%
See 4 more Smart Citations
“…Disruption of this secretion system results in a reduction of the virulence potential of a number of bacteria including Klebsiella pneumoniae, Proteus mirabilis, Citrobacter rodentium and Salmonella enterica (Burall et al, 2004;Selkrig et al, 2012;Struve et al, 2003). The TamA/B complex is required for the efficient secretion of specific autotransporter proteins to the outer membrane in Enterobacteriaceae (Selkrig et al, 2012), in contrast to what is observed in morC mutants of A. actinomycetemcomitans, which express WT levels of known autotransporters (Smith et al, 2015a), which can easily be visualized by electron microscopy (Azari et al, 2013;Gallant et al, 2008).…”
Section: Introductionmentioning
confidence: 75%
“…A recent quantitative membrane proteomic study revealed a consistent decrease in the abundance of the proteins of the fimbrial secretion apparatus in the morC mutant strain when compared with the parent strain (Smith et al, 2015a). To fully comprehend the significance of these results, it was necessary first to determine the molecular basis of the defect that caused the afimbriation of the parent strain and secondly to complement and restore fimbrial production.…”
Section: Identification Of the Defect In Fimbriae Productionmentioning
confidence: 99%
See 3 more Smart Citations